A influência da composição do comércio na desigualdade de renda e índices de pobreza para o Brasil e suas regiões na década de 1990 - Guedes, Nádia Maria Silva (2006)
This study it aims at to analyze the influence of the relative endowment of the factors on the composition of the exportations, to identify the main factors that influence the growth of the income, the inequality and poverty and to evaluate the effect of the openness on these indicators, considering six groups of distinct samples: Brazil, Region North, Northeast, Center-west, Southeast and South, in the decade of 1990. The theories on economic Growth, Inequality and Poverty, Politics of reduction of the inequality of income and commercial Opening and economic development are the main beddings of this study. The results show that in Brazil the structure of relative endowment of the factors favors, mainly, the exportations of basic and manufactured products. In relation to the effect of the composition of the commerce, it was verified that the exportations of basic products can increase the income concentration, but reduce the index of poverty and its degree of severity. On the other hand, the exportations of semi manufactured and manufactured products tend to reduce the average income, to increase the index of poverty and its degree of severity. In that if it relates to the average income, the exportations of basic products had not presented well definite effect, provoking reductions in the average in Brazil and increasing in the Northeast, Center-West, Southeast and South. Finally, one perceived that the openness can increase the level of average income, reducing of the poverty index and its degree of severity; however it increases the degree of income concentration.